PSYCHOLOGICAL DEVELOPMENT OF LEADERSHIP COMPETENCE IN STUDENTS - Kurbanova Surayyo Tuynazar kizi (Bright Mind Publishing, 2025)
In this article, the psychological features of the formation and development of leadership competence in students are deeply studied. The article also identifies such psychological indicators as emotional intelligence, self-awareness, social adaptability, initiative, and decision-making ability as the main factors directly influencing the leadership potential of students.
Keywords: Leadership, competence, emotional intelligence, adaptability, initiative, social environment.